“DEMONIC MOTHER” AS TMOTIONAL AND CONTEXTUAL DOMINANT IN “DROWENED” BY TARAS SHEVCHENKO: PSYCHOLINGUISTIC ASPECT - Bukatchuk, Ch. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article defines and highlights peculiarities of psycholinguistic demonstration of emotional and contextual dominant of “Demonic Mother” in textual structure of “Drowned” by Taras Shevchenko by looking through the prism of affective and exalted accentuation of linguistic subject; linguistic representations and methods are described.